2009
DOI: 10.1007/s12199-009-0095-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of subjective symptoms of Japanese patients with multiple chemical sensitivity using QEESI©

Abstract: Objectives The Quick Environment Exposure Sensitivity Inventory (QEESI Ó ) has been used as a questionnaire to evaluate subjective symptoms of patients with multiple chemical sensitivity (MCS), also known as idiopathic environmental intolerance, in Japan. However, no cutoff value for Japanese subjects has yet been established. We designed this study to establish a cutoff value for Japanese subjects using QEESI Ó for screening of MCS patients. Methods A questionnaire using the QEESI Ó was administered to 103 MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 19 publications
1
26
2
Order By: Relevance
“…Hojo et al designed a study to establish the cut-off value for Japanese using the QEESI for screening MCS patients [24]. The cut-off values for Japanese subjects were determined to be ≥40 for the chemical sensitivity subscale, ≥20 for the symptom severity subscale, and ≥10 for the life impact subscale.…”
Section: Methodsmentioning
confidence: 99%
“…Hojo et al designed a study to establish the cut-off value for Japanese using the QEESI for screening MCS patients [24]. The cut-off values for Japanese subjects were determined to be ≥40 for the chemical sensitivity subscale, ≥20 for the symptom severity subscale, and ≥10 for the life impact subscale.…”
Section: Methodsmentioning
confidence: 99%
“…In the past, we [Hojo, 2002; Hojo et al, 2003, 2004, 2005, 2007, 2008a, 2008b, 2009; Hojo and Tokiya, 2012] conducted several investigations in order to elucidate the actual status of multiple chemical sensitivity (MCS) and sick building syndrome or sick house syndrome (SHS) patients in Japan using the quick environmental exposure and sensitivity inventory (QEESI) developed by Miller and Prihoda [1999]. Our findings revealed that a number of MCS/SHS patients complained of hypersensitive reactions to various EMF sources.…”
Section: Introductionmentioning
confidence: 99%
“…When Hojo et al [17] confirmed that the QEESI is effective for screening Japanese MCS patients, they suggested that the cutoff values for Japanese subjects should be chemical sensitivity score C40 and symptom severity score C20. In our study population, 4.3% (n = 47) of the subjects met that criteria and were defined as the cases (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Hojo et al [17] designed a study to establish a new cutoff value for Japanese using the QEESI for screening of MCS patients. According to that study, one difference from patients in America was that in Japanese patients the other chemical sensitivity subscale had low sensitivity and low specificity.…”
Section: Subjectsmentioning
confidence: 99%